Parent-of-origin effects of phosphatidyl inositol-bisphosphate hydrolysis pathway genes on type 2 diabetes and the modification effect by obesity - Tan, Yinxi; Peng, Hexiang; Wang, Siyue; Hu, Poning; Zheng, Yi; Zhang, Haodong; Guo, Huangda; Li, Yixin; Zhang, Hanyu; Wu, Yiqun; Qin, Xueying; Li, Jing; et al. (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the parent-of-origin effects (POEs) of genes in the phosphatidyl inositol-bisphosphate (PIP2) hydrolysis pathway on type 2 diabetes (T2D) and preliminarily assess whether environmental factors may modify these effects.MethodsBased on data from an ongoing family-based cohort in Beijing, genetic information of 162 individuals from 53 case-parent triads was used to examine the POE of single nucleotide polymorphisms (SNPs) in the PIP2 pathway on T2D using maximum likelihood estimation based on a log-linear model. Stratified analyses were performed to assess the potential modification of POE by environmental factors, including smoking, drinking, and body mass index (BMI). Further enrichment analysis was conducted based on the POE results.ResultsA total of 214 SNPs from the PIP2 hydrolysis pathway had nominally significant (P < 0.05) POE on T2D, among which rs199684931 (RRm/RRp = 0.28, Pinteraction = 0.03), rs4750491 (RRm/RRp = 4.67, Pinteraction = 0.04), rs1090705 (RRm/RRp = 0.21, Pinteraction = 0.04), rs9663645 (RRm/RRp = 4.75, Pinteraction = 0.04), and rs200488869 (RRm/RRp = 4.75, Pinteraction = 0.04) from PRKCQ exhibited POE–BMI interactions. Specifically, maternal POE was reduced for rs199684931 and rs1090705 in individuals with higher BMI levels, while it increased for rs4750491, rs9663645, and rs200488869 in higher BMI groups. Additionally, 72 of the 214 significant POE SNPs were recognized as methylation quantitative trait loci, hinting at a possible role in regulation. The enrichment analysis validated these findings and the role of the genes in lipid metabolism.ConclusionThe current study provides a preliminary hint that SNPs in the PIP2 pathway genes may exhibit POE on T2D, contributing to its heritability. Notably, five SNPs in the PRKCQ gene demonstrated a potential interaction between POE and BMI on T2D. Further research is necessary to explore the underlying molecular mechanisms and to validate these findings in larger and independent populations.